(untitled) (International Journal of Food and Nutritional Sciences, 2021)
The nature of party system in the federal units of India/ states have kept evolving with the changing times and circumstances. The parliamentary democracy within the framework of federalism has its own socio-economic and socio-Political implications which are intertwined. Therefore, changes within the political system at the macro/ micro level are generally, if not necessarily, reflected at the micro/ macro levels as well. This is evident in the nature of political competition in Indian party system as well. The sudden blow to the Indian National Congress and the predominant party system at the state level which began in 1960s ultimately led to coalition politics at the national level.The researcher has tried to understand and explain this phenomenon during the era of coalition in the context of Bihar.